A Critical Assessment of the European Cultural Approach to Counter Terrorism - Marsili, M. (Europe as a Global Actor (EGA), 2016)
The wave of jihadism affecting western countries since 11 September 2001, has pushed governments to pass repressive legislation, which is restrictive on fundamental rights and freedoms. The EU security and counter-terrorism strategy has not been effective, instead resulted in the increase of affiliations to jihadist groups in Europe. Little or nothing has been done to develop a successful media and communication strategy. Little or nothing has been done to try to understand why many Europeans - grown and often born in western countries - turned themselves into 'lone wolves' or 'foreign fighters'. What pushed these 'lost sons of Europe' to walk the path of terrorism? What are the causes of radicalisation, and how can we remedy them? This paper suggests some explanations based on sociology and urban sociology. The essay tackles important and timely concerns in contemporary security studies, and gives a critical assessment of the European cultural approach to counter terrorism, suggesting a holistic and comprehensive strategy to address it.